Peradaban Islam Di Asia Selatan - Yahya , Mohammad Alfan Choirudin; Dinda Aisyah Huwaina Humaira Pratolo; Delia Anggun Sasmita; Umar Al-Faruq (GLOBAL SCIENTS PUBLISHER, 2024)
This study aims to analyze the process of entry and development of Islam in South Asia, especially its influence on culture, society, and politics in the region. This study also aims to understand the interaction between Islamic culture and local traditions, such as Hinduism, as well as the contribution of Islam in shaping regional identity, including through cultural acculturation, such as the birth of Urdu and the development of Sufism. In addition, this study aims to provide a comprehensive picture of the historical dynamics that occurred in South Asia as an effort to enrich the study of Islamic history and culture in the region. This study uses a qualitative method based on library research to examine relevant written sources, such as books, journals, articles, and other sources. The stages of analysis include topic selection, data collection and filtering (heuristics), in-depth analysis (interpretation), and writing (historiography). The results of the study show that the entry of Islam brought major changes to the social and political systems of South Asia, especially through the contributions of Islamic kingdoms such as the Mughal Empire. However, the influence of Hinduism is still felt in aspects of social stratification and mysticism. The phenomenon of Sufism reflects the interaction between Islamic and Hindu traditions, showing the diversity and dynamics of culture in the region. The conclusion of this study emphasizes the importance of understanding cultural acculturation in South Asian history as a reflection of the interaction between various civilizations. This study is expected to provide new insights for the study of the influence of Islam in South Asia and open up opportunities for further research on its influence in modern times.